Extensive CRISPR RNA modification reveals chemical compatibility and structure-activity relationships for Cas9 biochemical activity. Issue 2 (4th December 2018) - O'Reilly, Daniel; Kartje, Zachary J; Ageely, Eman A; Malek-Adamian, Elise; Habibian, Maryam; Schofield, Annabelle; Barkau, Christopher L; Rohilla, Kushal J; DeRossett, Lauren B; Weigle, Austin T; Damha, Masad J; Gagnon, Keith T
Abstract: CRISPR (clustered regularly interspaced short palindromic repeat) endonucleases are at the forefront of biotechnology, synthetic biology and gene editing. Methods for controlling enzyme properties promise to improve existing applications and enable new technologies. CRISPR enzymes rely on RNA cofactors to guide catalysis. Therefore, chemical modification of the guide RNA can be used to characterize structure-activity relationships within CRISPR ribonucleoprotein (RNP) enzymes and identify compatible chemistries for controlling activity. Here, we introduce chemical modifications to the sugar–phosphate backbone of Streptococcus pyogenes Cas9 CRISPR RNA (crRNA) to probe chemical and structural requirements. Ribose sugars that promoted or accommodated A-form helical architecture in and around the crRNA 'seed' region were tolerated best. A wider range of modifications were acceptable outside of the seed, especially D -2′-deoxyribose, and we exploited this property to facilitate exploration of greater chemical diversity within the seed. 2′-fluoro was the most compatible modification whereas bulkier O -methyl sugar modifications were less tolerated. Activity trends could be rationalized for selected crRNAs using RNP stability and DNA target binding experiments. Cas9 activity in vitro tolerated most chemical modifications at predicted 2′-hydroxyl contact positions, whereas editing activity in cells was much less tolerant. The biochemical principles of chemical modification identified here will guide CRISPR-Cas9 engineering and enable new or improved applications.